2018
DOI: 10.21837/pmjournal.v16.i7.508
|View full text |Cite
|
Sign up to set email alerts
|

Lost Space in Urban Core Areas of Kuala Lumpur in Relations to Physical Urban Environment

Abstract: The process of urban development today treats buildings as isolated objects, not as part of the larger fabric of streets, squares, parks and viable open space, and without an understanding of human behaviour. What emerges in most environmental settings is unshaped antispace. The essence of this research seeks to establish a better understanding towards the local perception of lost space in the urban core areas of Kuala Lumpur and identify the appropriate tools to improve the usability of the space. The researc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 3 publications
0
7
0
Order By: Relevance
“…In Malaysia, there still exist indigenous tribes that live in remote areas, such as the Bateq tribe in the vicinity of Kelantan and Pahang, the Mendiq tribe in Kelantan, and the Senoi people around the slopes of the Titiwangsa mountain range, specifically in the hinterlands of Perak, Kelantan, and Pahang. Previous studies have shown that factors such as poverty and a preference for living in remote areas contribute to the occurrence of educational dropout (Khalid et al, 2018). According to Yusoff et al (2019), who studied the Jahai indigenous community in the state of Perak, economic development among the population still remains below the poverty line, with an average household income of less than RM500 per month.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In Malaysia, there still exist indigenous tribes that live in remote areas, such as the Bateq tribe in the vicinity of Kelantan and Pahang, the Mendiq tribe in Kelantan, and the Senoi people around the slopes of the Titiwangsa mountain range, specifically in the hinterlands of Perak, Kelantan, and Pahang. Previous studies have shown that factors such as poverty and a preference for living in remote areas contribute to the occurrence of educational dropout (Khalid et al, 2018). According to Yusoff et al (2019), who studied the Jahai indigenous community in the state of Perak, economic development among the population still remains below the poverty line, with an average household income of less than RM500 per month.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Economic activity refers to the potential for UVs to generate economic and fiscal benefits for the local community through business growth, job creation, and neighbourhood improvement (Hashem et al, 2022;Hwang & Lee, 2020). Seal refers to the extent to which an urban void (UV) is physically accessible or open to the public (Elbeah et al, 2022;Khalid et al, 2018). Open UVs are easily accessible and can be freely entered, while closed UVs are not easily accessible or are physically blocked.…”
Section: Classification Criteriamentioning
confidence: 99%
“…City lifestyle with hectic schedule and unpleasant environments, such as concrete jungle, lack of green space, urban heat island's effect, noise and slump, will lead to stress and may trigger mental disorder. Moreover, open spaces are slowly replaced by highways, thoroughfares, and parking bays which are considered as predominant types of open spaces in the modern urban planning perspectives (Khalid et al, 2018). The scientists found that residents who grew up with the least green space within the neighbourhood, had as much as a 55 percent increased risk of developing psychiatric disorders (NASA, 2019).…”
Section: Stress Due To Lack Of Green Space and Higher House Rental In The Citymentioning
confidence: 99%